Penerapan Sistem E-Learning Melalui Aplikasi Edmodo dalam Meningkatkan Motivasi Belajar Mahasiswa Program Studi Pendidikan Bahasa, Sastra Indonesia dan Daerah di Universitas Mathla’ul Anwar Banten - Purlilaiceu, Purlilaiceu (Universitas Mathla'ul Anwar Banten, 2018)
This research was conducted to obtain data about how the application of e-learning system through Edmodo application in improving student learning motivation in the language education program, Indonesian and regional literature at Universitas Mathla’ul Anwar Banten. The purpose of the study was to determine the effectiveness of the application of the e-learning system through the Edmodo application in improving student learning motivation. The methodology used in this study is descriptive analysis, meaning that the data obtained from the sample population of the study will be described and analyzed and then interpreted. In other words that analytical descriptive method is a method that aims to describe or give an overview of an object of research that is examined through samples or data that has been collected and make generally accepted conclusions. The sample data used in this study amounted to 56 students, while sampling was done using the “Random sampling” technique. The results obtained are through questionnaires distributed to students with the Google Drive application so that data can be obtained about student learning motivation with the e-learning system through the Edmodo application. The results of the study prove that student learning motivation is very high by using the e-learning system, it's just that the frequency of using Edmodo applications in learning must be improved.